WORMLIKE MIECLLES AS A MOBILITY CONTROL AGENT IN CHEMICAL EOR - ., SANDEEP (2013)
Mobility control is one of the most important parameter in chemical EOR. The partially hydrolyzed polyacrylamides (HPAM) polymers are extensively used for it, but HPAM polymers are degradable at critical parameters of reservoir.